Answer:
2
Step-by-step explanation:
We can find the average rate of change by using the formula
rate of change = (y2-y1) /(x2-x1)
= (5-3)/(1-0)
= 2/1
=2
<span>There is a formula for a loan : A = P * r * ( r + 1 ) ^n / (( r + 1 ) ^n - 1 ), where P is the loan and A is the monthly payment. So P = $4,250 and r = 0.1325 : 12 = 0.011. ( 13.25 % = 0.1325 and we divide it by 12, because the interest is compounded monthly ). A = 4,250 * 0.011 * 1.011^(24) / ( 1.011^(24) - 1 ) = 4,250 * 0.11 * 1.3 / 0.3 = 4,250 * 0.0477; A = $202.55. Finally we have to multiply this sum by 24 : the total finance charge: $202.55 * 24 = $ 4,861.20. Answer: D ) $4,861.20 </span>
Answer:
Step-by-step explanation:
lol
I’am doing this rn it’s soooo hardddd!! Let me see if I know this one